Changes in motor cortical excitability in patients with Sydenham's chorea. Issue 2 (7th June 2014) - Khedr, Eman M.; Ahmed, Mohamed A.; Ali, Anwar M.; Badry, Reda; Rothwell, John C.; Stacy (Chair), Mark; Lang, Anthony; Napier, Celeste; Samuel, Michael; Strafella, Antonio; Weintraub, Daniel
ABSTRACT Background and Purpose The neurophysiological characteristics of motor cortex have been well characterized in patients with Huntington's disease. We present the first data on cortical excitability in patients with Sydenham's chorea. Methods Motor cortex excitability was examined using transcranial magnetic stimulation in 16 patients in the early clinical stages of Sydenham's chorea and in 17 age‐ and sex‐matched control subjects. Investigations included resting and active motor threshold, motor evoked potential, input–output curves, contralateral silent period, and transcallosal inhibition. Results Resting and active motor threshold were significantly higher and motor evoked potentials were significantly smaller in patients in comparison with controls. The input–output curves were shallower in both hemispheres of patients with chorea compared with controls. No significant differences were seen in silent period or transcallosal inhibition duration. Conclusion Sydenham's chorea is characterized by reduced excitability of corticospinal output similar to that observed in Huntington's disease. © 2014 International Parkinson and Movement Disorder Society